فعالية استخدام برنامج قويزيليز كويسلة التقويم في تعليم مهارة القراءة في المدرسة العالية الحكومية الثامنة جومبانج - Abidah, Nur Alfi; Setyabudi, M Arif (Lembaga Yasin AlSys, 2025)
Arabic language instruction in schools often encounters challenges, particularly in developing reading skills. Many students struggle to comprehend Arabic texts, and the evaluation methods commonly employed remain limited in scope. With the advancement of technology, applications such as Quizalize offer a more interactive and engaging alternative for assessment. This study aims to examine the use of the Quizalize application and its effectiveness as an evaluation tool in Mahārah Qirāʾah learning at MAN 8 Jombang. A quantitative research method was employed, using a quasi-experimental design specifically, the Quasi One-Group Pretest-Posttest model. Data were collected through observation, testing, and documentation. The findings indicate: (1) the use of Quizalize as an evaluation medium for reading skills in Arabic language instruction at class XI 2 MAN 8 Jombang facilitated interactive and engaging assessments, enhancing both teacher efficiency and student participation in the learning process; (2) the effectiveness of Quizalize in assessing Mahārah Qirāʾah was evident. Descriptive analysis revealed an increase in average scores from 70 (pretest) to 91.1 (posttest). Hypothesis testing showed an Asymp. Sig value of < 0.001, indicating that the use of Quizalize was proven effective in evaluating Mahārah Qirāʾah instruction.